Hypoxia-inducible factor-1α polymorphisms link to coronary artery collateral development and clinical presentation of coronary artery disease - Liu, Qian; Liang, Yun; Zou, Ping; Ni, Wei-xin; Li, Yu-guang; Chen, Song-ming (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
AIMS: This study aimed to investigate the association of Hypoxia-inducible factor-1α (HIF-1α) C1772T and G1790A single nucleotide polymorphisms (SNPs) with: incidence, clinical type, severity of coronary atherosclerosis and coronary collaterals of coronary artery disease (CAD). METHODS: The clinical data and genomic DNA were gathered in 958 subjects, including 560 controls and 398 patients with CAD. CAD was confirmed with coronary angiography (CAG). The genotypes for two SNPs were determined by high resolution melting after PCR amplification. RESULTS: Neither the HIF-1α C1772T nor the G1790A genotype was significantly associated with CAD and, no gene-gene or gene-environmental interactions were identified. However, both HIF-1α C1772T and G1790A (P<0.05) alleles were associated with clinical type and formation of coronary collaterals (P<0.05). Patients carrying genotype CT (P=0.019, OR=4.905,91, 95% CI: 1.355-17.761) and GA (P=0.026, OR=3.052, 95% CI: 1.180-7.892) had signiﬁcantly higher stable angina pectoris (SAP) than unstable angina pectoris (UAP) and acute myocardial infarction (AMI). The presence of HIF-1 genotype CT (P=0.016, OR=13.373, 95% CI: 15.468-32.709) and GA (P=0.001, OR=19.741, 95% CI: 8.125-47.966) predicted lower collateral formation and severity of CAD secondary to the absence of collaterals (r=0.242, P<0.001). CONCLUSIONS: We conclude that functional polymorphisms in the HIF-1α gene do not modify CAD risk but they are associated with the formation of coronary collaterals and clinical presentation of CAD.
Keywords: Genotype; Female; Collateral Circulation; Coronary Vessels; ženské pohlaví; jednonukleotidový polymorfismus; lidé; faktor 1 indukovatelný hypoxií - podjednotka alfa; Polymorphism, Single Nucleotide; genotyp; stupeň závažnosti nemoci; koronární cévy; Incidence; kolaterální oběh; nemoci koronárních tepen; Male; incidence; Aged; Coronary Artery Disease; Hypoxia-Inducible Factor 1, alpha Subunit; lidé středního věku; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; Humans